Effects of Cucumber Mosaic Virus on Yield Components and Yield of Bambara Groundnut - S.M, Buhari; M.T, Salaudeen; A.C, Wada (Bulletin of Scientific Research, 2022)
Bambara groundnut (Vigna subterranean L. Verdc) is a leguminous plant and its seeds are highly nutritious and can be considered as complete food. In addition to being a neglected crop; its production is limited by several constraints among which virus diseases are the most implicated. In order to contribute to the improvement of bambara groundnut in Nigeria, landraces of bambara groundnut were screened for resistance to Cucumber mosaic virus (CMV), one of the most damaging viruses in grain legumes. Treatments consisted of five landraces namely Black, Brown, Cream, Red nav, and Zebra coloured got from local farmers. These were arranged in Randomised Complete Block Design, with three replicates. Seedlings were infected with CMV isolate three weeks after sowing (WAS), during the 2019 and 2020 trials. The infected plants exhibited various symptoms of chlorosis, leaf deformation, growth retardation, and plant stunting. The sCMV caused significant reduction in plant height, the number of branches, leaves, pods, and seeds weight. In the 2019 and 2020 trials, 100 % incidence with the highest severity was observed in the Bambara groundnut landraces. Disease incidence varied between 41.6% in “Black” and 95.8 % in “Cream,” while disease severity was higher in “Cream” and “Red nav” with 5.0 respectively. “Black” and “Zebra” were the tallest with 16.8 cm among the infected as well as disease-free with 22.6 cm tall plants. “Black” landrace produced the highest number of pods in both CMV infections with 21 and disease-free with 33 pods respectively. Conversely, the number of days to flowering of 43 days was highest in infected plants of “Black”. The “Black” and “Zebra” landraces recorded uniform seed weights and the highest seed weight under CMV infection with 1.7 g per plant. The impact of the virus on yield loss was lowest in “Black” and “Zebra” landraces which indicated their possible use in the management of Cucumber mosaic virus disease in Bambara groundnut.